Short-term and Long-term Postoperative Safety of Off-Pump versus On-Pump Coronary Artery Bypass Grafting for Coronary Heart Disease: A Meta-analysis for Randomized Controlled Trials - Luo, Taobo; Ni, Yiming (The Thoracic and Cardiovascular Surgeon, 2015)
Objective The aim was to compare the short-term (30 days after surgery) and long-term (over 6 months' follow-up) postoperative safety of off-pump and on-pump coronary artery bypass grafting (CABG) for patients with coronary heart disease (CHD).Methods Relevant randomized controlled trials (RCTs) were obtained from PubMed, Embase, Springer, Ovid, and Cochrane library up to July 2013. Odds ratios (ORs) with their 95% confidence intervals (CIs) were used to access effect sizes.Results Seven RCTs involving 9,128 patients were included. Results suggested no significant difference in all the short-term outcomes (mortality, OR = 0.90, 95% CI: 0.69 to 1.16, p = 0.41; myocardial infarction, OR = 0.95, 95% CI: 0.79 to 1.15, p = 0.61; stroke, OR = 0.78, 95% CI: 0.56 to 1.07, p = 0.12; renal failure, OR = 0.84, 95% CI: 0.60 to 1.18, p = 0.43; revascularization: OR = 1.95, 95% CI: 0.79 to 4.85, p = 0.15) and some long-term outcomes (mortality, OR = 1.02, 95% CI: 0.86 to 1.22, p = 0.81; myocardial infarction, OR = 0.86, 95% CI: 0.70 to 1.04, p = 0.12; stroke, OR = 0.89, 95% CI: 0.67 to 1.19, p = 0.44) between off-pump and on-pump CABG. However, off-pump CABG had a significantly higher revascularization rate (OR = 1.45; 95% CI: 1.02 to 2.06; p = 0.04) than on-pump CABG in long-term follow-up.Conclusion Short-term postoperative safety was similar between off-pump and on-pump CABG. A high revascularization rate was the drawback of off-pump CABG for CHD patients in long-term follow-up.
Keywords: coronary heart disease; off-pump coronary artery bypass grafting; on-pump coronary artery bypass grafting; clinical outcomes; postoperative safety